2020
DOI: 10.31557/apjec.2020.3.1.1-7
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Cancer Protection by Most Recommended International Administrative Control

Abstract: Background and purpose: Microwave and radio waves are a class of non-ionizing beams that have a variety of applications in different environments, and uncontrolled exposure to these beams can lead to cancer. Implementation of management measures can result in lower exposure and acceptable efficiency in controlling occupational exposure to these beams. Using a descriptive review, this study examines the most managerial measures recommended by international organizations to control occupational exposure to these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(3 reference statements)
0
1
0
Order By: Relevance
“…Moreover, many reports have shown that healthcare organizations worldwide suffer from poor quality, high cost, and ineffective practices due to inadequate time management, especially in oncology settings (Ramireddy et al, 2017;Vashistha et al, 2019;Zaker et al, 2019;Zaroushani et al, 2020;Zoure et al, 2020). This calls for further studies to discuss the factors that can significantly affect the adoption of lean management and improve the outcome in the healthcare setting.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many reports have shown that healthcare organizations worldwide suffer from poor quality, high cost, and ineffective practices due to inadequate time management, especially in oncology settings (Ramireddy et al, 2017;Vashistha et al, 2019;Zaker et al, 2019;Zaroushani et al, 2020;Zoure et al, 2020). This calls for further studies to discuss the factors that can significantly affect the adoption of lean management and improve the outcome in the healthcare setting.…”
Section: Introductionmentioning
confidence: 99%